Performance analysis of an Organic Rankine Cycle system with superheater utilizing exhaust gas of a turbofan engine - A M Nasir, N; Saadon, S; R Abu Talib, A (International Journal of Engineering and Technology, 2018)
Waste heat recovery is recognized as one of the methods to overcome this energy saving issue. In this paper, the Organic Rankine Cycle (ORC) system has been introduced for the waste heat recovery. The main objective of the study is to convert the unused heat into useful power, which could reduce the fuel consumption and also minimize the harmful exhaust transmission. A thermodynamic model of the waste heat recovery cycle is developed and validated. The eventual results depict a reasonable agreement for the ORC power output and its thermal performance, especially at higher turbine inlet pressure. Consequently, this ORC model is then connected to a turbofan engine. The performance analysis of the engine depicts that the lowest Thrust Specific Fuel Consumption (TSFC) is at 0.68 lbm/lbf.h with the thrust force of 7000 lbf, thus lower than the base cycle without ORC as waste heat recovery.Â Â